On the proper essence of Christian economic ethics - Rainer Kreuzhof; Wolfgang Ockenfels (Management Revue, 2010)
In recent times, the question about the proper essence of a Christian economic ethics has rarely been asked explicitly. However, the concept of a post-secular society, as presented by Jürgen Habermas, offers renewed access. The necessary foundation for this approach involves the relationship between belief and reason as the basis for communication, the concept of 'being made in God's own likeness' as regulating factor and the association with the Christian way of life as a prerequisite for responsible economic activity. One possible consequence hereof is to see the social market economy as a third way, situated between socialism and capitalism, with its extra-economic prerequisites and its particular relationship between market and state. After all, the aim is also to consider the role of the Church as a global player and an intermediary of values for a civil society.
Keywords: 650; Christian economic ethics; Catholic Social Teaching; post-secular society; political theology; social market economy